Production System and Technology Adoption Profile of Black Pepper Cultivation in Kerala - Rejula, K; Lijo, T; Rajeev, P (Journal of Agricultural Extension Management, 2018)
Within India, Kerala is the spice garden. However, the pepper cultivation system in Kerala is now handicapped by a number of problems. The yield of this crop has declined mainly due to senile plantations and minimum input use, on account of declining market price and declining profit margin. The present study was undertaken covering three districts of Kerala through a sample survey to study the features of the production system and track major shifts, study the technology adoption profile of the farmers and identify major constraints as perceived by the farmers. Around 38 per cent of the farmers adopted organic production system and technology adoption profile showed a less input intensive approach. Even though 60 per cent of farmers practiced rain fed cultivation, 15 per cent fully irrigated and 25 per cent adopted irrigation partially. Majority of the farmers were holding land between 80 cents to 4.5 acres. Around 40 per cent of the total vine population was in the pre-bearing stage. There is slow and gradual increase in adoption rate of improved varieties and majority of the farmers sourced new planting material from own fields, showing less dependence on public and private nurseries. The major field problems reported by the farmers are pre-bearing loss of the vines, and many biotic problems like pest and disease incidence and environmental problems like shifts in climate especially rainfall.